The eastward propagation of hourly rainfall at the western edge of the Hengduan Mountains and its leading circulation patterns during the warm season - Hao Wu; Wei Hua; Xiaofei Wu; Weihua Yuan (Meteorological Applications)
Abstract The Hengduan Mountains, which comprise numerous north–south‐oriented mountains, exhibit unique precipitation characteristics and obvious regional differences. Based on the Global Precipitation Measurement (GPM) dataset, hourly rainfall features in the Hengduan Mountains during the warm season (May–September) from 2001 to 2021 were investigated. A key region with relatively large rainfall amounts and unique morning peaks was found at the western edge of the Hengduan Mountains (WEHM). The diurnal rainfall peaks showed an eastward delay from northern Myanmar to the WEHM. Less frequent long‐duration events (longer than 6 h) contributed more than 58% to the cumulative precipitation amount at the WEHM. Moreover, long‐duration rainfall exhibited similar eastward propagation features, which were further verified by the hourly variations in the rainfall amount and black‐body temperature on long‐duration rainfall days. Short‐duration rainfall events accounted for below 20% of the cumulative precipitation and presented late‐afternoon diurnal peaks at the WEHM. ERA5 data were employed to explain the rainfall propagation signal. The results indicated that the upstream low‐level wind field significantly influences the diurnal variation of rainfall at the WEHM, and wind anomaly rotation from night to early morning contributed to the eastward delay in the onset of long‐duration rainfall. In general, this work could contribute to a deeper comprehension of the precipitation characteristics and formation of morning rainfall over the WEHM.